Efeito de pequenas variações na altitude e na ordem de riachos sobre a estrutura de comunidades de insetos aquáticos - Braun, Bruna Marmitt (2014)
The present study analyzes the effects of a short elevation gradient (0-500 m) and stream order (1st to 4th) on the structure and spatial distribution of EPT and Coleoptera (Elmidae and Psephenidae) communities in a Neotropical temperate basin. The influence of local abiotic factors on the communities was also analyzed. Forty streams (from 1st to 4th order) distributed in five elevation ranges (0-100 to 400-500 m) were sampled. Overall, 52 genera belonging to 18 families were recorded. The highest richness was found in intermediate elevation ranges and 1st and 4th order streams. Most abiotic factors were structured according to the elevation gradient. Air temperature, stream order and electrical conductivity were related to the distribution of the following genera: Americabetis, Camelobaetidius, Paracloeodes and Smicridea. The caddisfly genera Austrotinodes and Celaenotrichia and an undescribed Elmidae genus (genus M) are new records for the region. The results evidence that even short elevation ranges (e.g. 100 m) may influence differences in community strucutre of environmentally sensitive aquatic insects. Short elevation gradients can also modulate variation in abiotic factors that influence the composition of stream communities. In this sense, intermediate elevation zones located in regions marked by low elevation gradients and low-order streams might deserve more consideration from conservation and environmental assessments programs.